Crystallography Analysis on LSCF and LSM-based Perovskite Oxides - Silvana Dwi Nurherdiana; Nikmatin Sholichah; Susilowati; Sukirmiyadi; Erwan Adi Saputro; Mohd Jumain Jalil; Hamzah Fansuri (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Perovskite oxide as a metal oxide offers an excellence on mixed ionic and electronic conductor (MIEC) properties which work simultaneously. The crystal structure of perovskite oxide plays the important role to achieve the superior performance. Generally, it formed a cubic which potentially distorted due to the ratio of metal ion constituents, the calcination temperature and the synthesis method used. Thus, this study presents chemical analysis of La0.7Sr0.3Co0.2Fe0.8O3-δ (LSCF) and La0.7Sr0.3MnO3-δ (LSM)-based perovskite oxides through crystallographic identification using Rietveld Refinement method (Rietica software) and material porosity analysis. The results show that the two types of perovskite oxide have different distorted crystal structures. Perovskite oxide LSCF produces hexagonal crystals and 63.98% rhombohedral dominance, while LSM remained significantly different from LSCF. LSM consist less hexagonal and 55.47% cubic structure. In addition, the pore characteristics indicate that macropores and pore volumes are more abundant in LSCF than LSM. This information can be used as a basis for the use of oxide materials as a separator of oxygen ions from the air, solid oxide fuel cells and catalyst for value-added chemical production from methane flue gas.